An Improved Method of Evidence Theory Based on Membership Function. Issue 3 (October 2020) - Xu, Lixing; Liu, Zhi; Gong, Bin; Deng, Yang
Abstract: Aimed at the two major problems of the basic probability assignment and conflict management in classical evidence theory, a basic probability assignment(BPA) based on membership function is proposed to alleviate the dilemma caused by the above two problems, and an example is given to show the effectiveness of this method.